A Neuron-Specific Antiviral Mechanism Modulates the Persistent Infection of Rice Rhabdoviruses in Leafhopper Vectors - Wang, Haitao; Liu, Ye; Mo, Lining; Huo, Chenyang; Wang, Ziyao; Zhong, Panpan; Jia, Dongsheng; Zhang, Xiaofeng; Chen, Qian; Chen, Hongyan; Wei, Taiyun (Frontiers in Microbiology, 2020)
Many plant rhabdoviruses are neurotropic and can persistently infect the central nervous system (CNS) of their insect vectors without causing significant cytopathology. The mechanisms by which the insect CNS resists infection by plant rhabdoviruses are largely unknown. Here, we report that the neural factor Hikaru genki homolog of the leafhopper Nephotettix cincticeps (NcHig) limits the spread of the nucleorhabdovirus rice yellow stunt virus (RYSV) in vector CNS. NcHig is predominantly expressed in the CNS of N. cincticeps, and the knockdown of NcHig expression by RNA interference enhances RYSV infection of the CNS. Furthermore, immuno-blockade of NcHig function by microinjection of N. cincticeps with NcHig antibody also enhances viral infection of the CNS. Thus, we conclude that the neuron-specific factor NcHig can control RYSV propagation in the CNS. Interestingly, we find the Hig homolog of the leafhopper Recilia dorsalis also has antiviral activity during the persistent infection of the cytorhabdovirus rice stripe mosaic virus (RSMV) in vector CNS. We further determine that RYSV and RSMV matrix proteins specifically interact with the complement control protein domains of Higs. Thus, the matrix protein-binding ability of Hig is potentially essential for its antiviral activity in rice leafhoppers. Our results demonstrate an evolutionarily conserved antiviral mechanism for Hig to mediate the persistent infection of rice rhabdoviruses in the CNS of leafhopper vectors.